A dual-targeted CeO2–DNA nanosensor for real-time imaging of H2O2 to assess atherosclerotic plaque vulnerability. Issue 16 (18th December 2019) - Liu, Zhenhua; Cao, Yujie; Zhang, Xiaona; Yang, Huazhen; Zhao, Yujie; Gao, Wen; Tang, Bo
Abstract : A novel dual-targeted CeO2 –DNA nanosensor by modifying with folic acid (FA) and CD36 antibody was designed. Abstract : A novel dual-targeted CeO2 –DNA nanosensor by modifying with folic acid (FA) and CD36 antibody was designed. This fluorescent nanosensor enables noninvasive imaging of alterations in H2 O2 in vitro and in vivo with good sensitivity and selectivity, accurately evaluating the inflammation level and providing early warning of plaque vulnerability.